Penatalaksanaan Holistik Skabies Pada pelajar Usia 14 Tahun melalui Pendekatan Kedokteran Keluarga - Aila Karyus; Nikom Sonia Purohita (Medula, 2021)
Scabies is a skin disease caused by Sarcoptei scabei mites hominis variety. According to WHO, an estimated 300 million people are currently infected with scabies globally, with a prevalence ranging from 0.2% to 71%. Scabies attacks community because it is transmitted easily through skin contact. There are various factors that can lead to the failure of management of patients with scabies. Therefore, proper holistic management using a family medicine approach is needed. This study is a case report with primary data obtained from anamnesis, physical examination, and home visit. Secondary data were obtained from patient medical records. Patient A, a 14 year old student complained itching between his fingers, especially at night since 3 months. He already looking for treatment three times but his symptoms have not decreased. Then an initial holistic diagnosis is carried out. Pharmacological and non-pharmacological management is carried out with the principles of patient-centered, family focused, and community-oriented. The intervention was done using posters and pamphlets, including general knowledge about scabies, how to maintain personal and environmental hygiene, how to use medicine properly, and how to prevent transmission in the community. After the pharmacological and non-pharmacological management, evaluation is carried out. There is an increase in knowledge and changes in behavior for both patients and his families. It can be concluded, holistic management with a family medicine approach is needed for the management of patients with scabies in order to support the success of therapy and prevent transmission to the community.